Ethnohistoric study of eastern James Bay Cree social organization, 1700-1850 - Morantz, Toby Elaine, 1943- (Book collections on Project MUSE., 1983)
Focuses on the northern Algonquian region of eastern James Bay, Quebec to determine the impact of the fur trade on the social patterning of its inhabitants.